A comparison of limited vs unlimited attempts with online homework grades in introductory statistics courses. (19th March 2022) - Stewart, Patrick
Abstract: Online homework programs allow professors to preset how many attempts per homework problem each student is allowed to have. Some professors prefer to allow a limited number of extra attempts, and others prefer to allow students to have an unlimited number of extra attempts. Do these preferences lead to a difference in average homework grades? To study this question, seven statistics courses over the Fall 2020 and Spring 2021 semesters were analyzed. The Fall semester had a limited number of extra attempts for each homework problem, and the Spring semester had an unlimited number of extra attempts. The results of the study conclude that there is no statistically significant difference in average homework grades for most homework assignments. In any homework assignment with a statistically significant difference, there was a quantifiably small difference.